USING RASCH ANALYSIS TO EXPLORE WHAT STUDENTS LEARN ABOUT PROBABILITY CONCEPTS - Zamalia Mahmud; Anne Porter (Department of Doctoral Program on Mathematics Education, Sriwijaya University, 2015)
Studentsâ€™ understanding of probability concepts have been investigated from various different perspectives. This study was set out to investigate perceived understanding of probability concepts of forty-four students from the STAT131 Understanding Uncertainty and Variation course at the University of Wollongong, NSW. Rasch measurement which is based on a probabilistic model was used to identify concepts that students find easy, moderate and difficult to understand.Â Data were captured from the e-learning Moodle platform where students provided their responses through an on-line quiz. As illustrated in the Rasch map, 96% of the students could understand about sample space, simple events, mutually exclusive events and tree diagram while 67% of the students found concepts of conditional and independent events rather easy to understand.Keywords: Perceived Understanding, Probability Concepts, Rasch Measurement ModelÂ DOI: dx.doi.org/10.22342/jme.61.1